PERALIHAN TANAH NGINDUNG YANG CACAT HUKUM DI PENGADILAN NEGERI YOGYAKARTA (Studi Kasus Putusan Perkara Nomor: 31/Pdt.G/2009/PN.YK) - , RA. Sekar Semanggi Kusumo, Kunthoro Basuki, S.H, M.hum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study aimed at identifying what became the basic rule so that the case of defective-in law transition of the Ngindung ground appeared and the effect from the cancelation of the transition. This is a normative juridical study which emphasized on the discussion of the current norm. In this study a literature review was done to get theories, views relevant with the case, to make this study complete a field study was conducted to find the data directly based on the reality The result of the study indicated that the basic rule which made the case of the defective-in law transition appear was because Mrs. Kariya Pawira gave a house located in the ground of Raden Mas Jaga Patra to her two nephews, named Mr Rubani (Defendant I) and Yadika (Defendant II) and some of the house was rent by Mrs. Rubani (Defendant I) and Yadika (Defendant II) to Mrs. Muryani (Defendant III) without the consent of the landowner. The legal consequence due to the cancellation of the transition was that any transition that appeared should be considered invalid and must be canceled. Mrs. Rubani (Defendant I) and Yadika (Defendant II) must dismantle the house and then return the land to Raden Mas Jaga Patraâs heirs. Mrs. Muryani had to go out without getting compensation for the money she had paid because initially Mrs. Muryani (Defendant III) didnât have any relation at all with the accuser. But have directly relation to Mrs. Rubani (Defendant I) and Yadika (Defendant II) so Mrs. Rubani (Defendant I) and Yadika (Defendant II) should bear on all the lose experienced by Mrs. Muryani.